(untitled) (Revista da Universidade Federal de Minas Gerais, 2021)
Extension, as well as Teaching and Research, is one of the three pillars of the public university in Brazil, and its guiding principle is the approach between the university and civil society. This article presents some innovations and trends in relation to these extension practices, considering not only the urgency imposed by the pandemic, but also the consolidation of forms of action already experienced in this area. For this, we supported the extension project “Building Places of Metropolitan Urbanity” of the School of Architecture at UFMG. It is intended, from the methodologies adopted in the pre-pandemic and during the current period, to report the challenges and strategies adopted under different conditions.